Why Aren't More Lebanese Women Working? - Elzir Assy, Angela; Sayed, Haneen (World Bank, Washington, DC, 2018)
Ensuring equitable access to jobs and reducing gender gaps is essential for putting MENA countries on the path to inclusive growth and stability. Giving women and girls the opportunity to succeed can transform societies and economies. Reducing gender gaps in employment can help economies diversify their exports; appointing more women onto banking supervision boards can challenge cozy group-think; and tackling gender inequality can reduce income inequality, which, in turn, can drive more sustainable growth. Improving access to jobs for women is also expected to generate positive externalities to the society, by facilitating human capital accumulation, health and nutrition gains for children through increased women-controlled incomes.